The political transformation of Gulf tribal states : elitism and the social contract in Kuwait, Bahrain and Dubai, 1918-1970s /: elitism and the social contract in Kuwait, Bahrain and Dubai, 1918-1970s. (2014) - Yanai, Shaul
No abstract available